A Space‐Time Conversion Vehicle for Programmed Multi‐Drugs Delivery into Pancreatic Tumor to Overcome Matrix and Reflux Barriers. Issue 20 (4th May 2022) - Huo, Taotao; Zhang, Xiaoyi; Qian, Min; Nie, Huifang; Liang, Dong; Lin, Chenteng; Yang, Yafeng; Guo, Wei; Lächelt, Ulrich; Huang, Rongqin
Abstract: The numerous biological barriers, which limit pharmacotherapy of pancreatic carcinoma, including inadequate drug accumulation in the tumor environment, a dense extracellular matrix (ECM) and efficient drug‐efflux mechanisms, illustrate the requirement of multifunctional delivery systems to overcome the individual barriers at the right place at the right time. Herein, a space–time conversion vehicle based on covalent organic framework (COF)‐coated mesoporous silica nanospheres (MSN) with a sandwiched polyethyleneimine (PEI) layer (MPCP), is designed. The space‐specific drugs‐loaded vehicle (MG PP CL P) is obtained by separately incorporating a chemotherapeutic agent (gemcitabine, G) into the MSN core, a P glycoprotein inhibitor (LY 335979, P) into the PEI layer, and an extracellular matrix disruptor (losartan, L) into the COF shell. Thereafter, a programmed drug delivery is achieved via the ordered degradation from COF shell to MSN core. Sequential release of the individual drugs, synergized with a change of nanoparticle surface charge, contribute to an obvious extracellular matrix distraction, distinct drug efflux inhibition, and consequently enhance chemotherapeutic outcomes in pancreatic carcinoma. This MPCP‐based vehicle design suggests a robust space–time conversion strategy to achieve programmed multi‐drugs delivery and represents a new avenue to the treatment of pancreatic carcinoma by overcoming extracellular matrix and drug reflux barriers. Abstract : A programmed drug delivery system (MG PP CL P) is obtained by spatially incorporating gemcitabine (G), P glycoprotein inhibitor (P), and losartan (L) into the MSN core, PEI layer, and COF shell, respectively, to achieve an extracellular matrix distraction, distinct drug efflux inhibition, and the enhanced chemotherapeutic outcomes for pancreatic carcinoma.